2019
DOI: 10.1177/2058739219840152
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of pterostilbene on ulcerative colitis in rats via suppressing NF-κB pathway and activating PPAR-γ

Abstract: Our study aimed to investigate the protective effects and potential mechanisms of pterostilbene on rats with ulcerative colitis (UC). We established 2,4,6-trinitrobenzenesulfonic acid (TNBS) induced colitis rat model. Rats were randomly divided into three groups, including control group, model group, and pterostilbene group (30 mg/kg). Disease activity index (DAI) including body weight, stool consistency, and gross bleeding was measured. The concentration of superoxide dismutases (SODs), glutathione superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Resveratrol (polyphenol flavonoids) isolated from the skin of red grape and suggested the protective effect against various inflammatory reaction. Pterostilbene ( trans -3,5-dimethoxy-4′-hydroxystilbene) is a stilbene, that is naturally occurring methoxylated analog of Revesterol, commonly found in blueberry ( Acharya and Ghaskadbi, 2013 ; Shi et al, 2019 ). Pterostilbene shows the higher bioactivity and bioavailability than resveratrol due to presence of two extra methyl group in the structure ( Supplementary Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol (polyphenol flavonoids) isolated from the skin of red grape and suggested the protective effect against various inflammatory reaction. Pterostilbene ( trans -3,5-dimethoxy-4′-hydroxystilbene) is a stilbene, that is naturally occurring methoxylated analog of Revesterol, commonly found in blueberry ( Acharya and Ghaskadbi, 2013 ; Shi et al, 2019 ). Pterostilbene shows the higher bioactivity and bioavailability than resveratrol due to presence of two extra methyl group in the structure ( Supplementary Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pterostilbene having the bioavailability (85%) as compared to the bioavailability of revesterol (20%) in animal model. Additionally, clinical studies showed that the pterostilbene may be a potent anti-inflammatory drug against various diseases ( Acharya and Ghaskadbi, 2013 ; Shi et al, 2019 ; Zhang et al, 2021 ). In this experimental study, we try to explore the neuroprotective and anti-inflammatory effect of pterostilbene against the MCAO rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Pterostilbene shows the higher bioactivity and bioavailability than resveratrol due to presence of two extra methyl group in the structure (Supplementary Figure S1). The structure of pterostilbene showed the removal of two hydroxy group with two methoxy group, which increase the bioactivity and oral bioavailability and demonstrate the prolong metabolism (Wu et al, 2017;Yang et al, 2017;Shi et al, 2019). Pterostilbene having the bioavailability (85%) as compared to the bioavailability of revesterol (20%) in animal model.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (polyphenol flavonoids) isolated from the skin of red grape and suggested the protective effect against various inflammatory reaction. Pterostilbene (trans-3,5dimethoxy-4′-hydroxystilbene) is a stilbene, that is naturally occurring methoxylated analog of Revesterol, commonly found in blueberry (Acharya and Ghaskadbi, 2013;Shi et al, 2019). Pterostilbene shows the higher bioactivity and bioavailability than resveratrol due to presence of two extra methyl group in the structure (Supplementary Figure S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation